Predictors of Entrepreneurship Intention Among Students in Vocational Colleges: A Structural Equation Modeling Approach - Wu, Xueshi; Tian, Yumi (Frontiers in Psychology, 2022)
The purpose of this study is to investigate the major drivers behind the entrepreneurial intention of students from higher vocational colleges in China. Total 424 respondents participated in the survey questionnaire that measured their self-reported responses to five constructs (entrepreneurial intention, entrepreneurial self-efficacy, emotional competencies, subjective norms, and entrepreneurial attitude). In addition to this, the equation modeling technique was used to perform the data analysis. The study results highlighted that both entrepreneurial self-efficacy and entrepreneurial attitudes serve as the significant predictors of entrepreneurial intention. Moreover, the entrepreneurial attitude was found to be a significant mediator of the entrepreneurial intention and emotional competencies. Finally, a model invariance was established across the female and male student samples. As a result, this study has put forward some implications regarding the entrepreneurship education of the higher vocational students in China.